Pengaruh Lingkungan Kerja terhadap Kinerja Guru SMP Negeri 24 Kota Jambi - Rasdi Rasdi; Muhammad Syukri (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study is to determine and describe the work environment and teacher performance at SMP N 24 Jambi City and to verify the effect of the work environment on teacher performance at SMP Negeri 24 Jambi City. The population used is the total number of teachers of SMP Negeri 24 Jambi City, amounting to 44 people. the sample is part of the population that is used as the object of research. The sample in the study was all teachers of SMP Negeri 24 Jambi City, totaling 44 people. Data collection methods in this study are field research and library research, in this study using descriptive analysis methods. Descriptive analysis method provides a systematic structure in organizing the data as well as objective answers and the data is presented in the form of an average, scale range. It is known that the constant value of 0.411 means that if the work environment variable (X) is 0 then the performance variable (Y) is 0.411. Furthermore, with the simple linear regression equation above, there is a positive value for the regression coefficient of the work environment variable, which is 0.657. work (X) is positive if there is a change in the work environment variable, it will cause a unidirectional change in the teacher performance variable. In this study, it can be analyzed the magnitude of the influence of the work environment on teacher performance that is equal to 0.657. it means that if the work environment (X) on teacher performance at SMP Negeri 24 Jambi City increases by 1%, the teacher's performance will increase 65.7%Â